ASOSIASI BUDAYA PATRIARKI TERHADAP PENGGUNAAN KONTRASEPSI - Wulandari, Dwi; Hadi, Ella Nurlaella (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, 2024)
The cultural culture that men are more dominant in society can influence the decision of women of childbearing age (WUS) in contraceptive use. This study aimed to determine the relationship between patriarchal culture and contraceptive use in Cipondoh Health Center, Tangerang City. This study was a quantitative study with a cross-sectional design, was conducted in May - June 2023, with a sample size of 210 WUS respondents who came to the Cipondoh Health Center and met the criteria. The number of samples was obtained based on sample calculations using the two proportions difference hypothesis test formula. Data was collected using a questionnaire sheet which was filled out independently by the respondent. The questionnaire contains questions on independent variables patriarchal culture in the family environment. The dependent variable is use of contraception. The results of the questionnaire were analyzed using the chi-square test. There was a relationship between patriarchal culture and contraceptive use at Cipondoh Health Center, Tangerang City (p= 0,005). Based on the OR value, it can be interpreted that women of reproductive age (WUS) with a culture that is not patriarchal, have a 3.58 times chance of using contraception compared to WUS who apply a patriarchal culture (OR = 3.58, 95% CI 1,904 - 6,748). It can be concluded that patriarchal culture influences the decisions of WUS in using contraception. There was a need to increase health communication and literacy regarding contraceptive use, to increase men’s knowledge and awareness so that they participate in using contraceptives.